GAFUR GHULAM IS A PATRIOTIC WRITER (European Journal of Interdisciplinary Research and Development, 2023)
Through this annotation, Gafur Ghulam's works are loved by the majority of readers of Uzbekistan and the world. Gafur Ghulam created a unique style by using the traditional styles of Uzbek literature in a modern style. In his works, he once again proves that he is a writer who loves and honors his nation.